IgM predominance in autoimmune disease: Genetics and gender (2012)
The role of specific immunoglobulin isotypes in human autoimmune disease has long attracted attention. Indeed, the presence of a polyclonal gammopathy is well known in a variety of systemic autoimmune diseases and is likely the result of chronic inflammation. However, in specific clinical situations, patients manifest isolated and elevated IgM levels, but normal IgG and IgA. The pathophysiology of this elevation and the clinical significance have been elusive. However, the relationships between specific genes and hyper-IgM are now very well defined, as it has been documented in primary hyper IgM syndromes. In this review we present data on clinical diseases with characteristic IgM abnormalities, including primary and secondary hyper IgM syndromes, autoimmune hemolytic anemia, cryoglobulinemia, primary biliary cirrhosis and multiple sclerosis and place the data in the perspective of the normal maturation of the immune response, including somatic mutation and genetic rearrangement. © 2011 Elsevier B.V.